Performance of 5-Strand Hamstring Autograft Anterior Cruciate Ligament Reconstruction in the STABILITY Study: A Subgroup Analysis. Issue 13 (November 2022) - Lodhia, Parth; Nazari, Goris; Bryant, Dianne; Getgood, Alan; McCormack, Robert; ,; Getgood, Alan M.J.; Bryant, Dianne M.; Litchfield, Robert; Willits, Kevin; Birmingham, Trevor; Hewison, Chris; et al.
Background: Anterior cruciate ligament (ACL) reconstructions (ACLRs) with graft diameters <8mm have been shown to have higher revision rates. The 5-strand (5S) hamstring autograft configuration is a proposed option to increase graft diameter. Purpose: To investigate the differences in clinical outcomes between 4-strand (4S) and 5S hamstring autografts for ACLR in patients who underwent ACLR alone or concomitantly with a lateral extra-articular tenodesis (LET) procedure. Study Design: Cohort study; Level of evidence, 2. Methods: Data from the STABILITY study were analyzed to compare a subgroup of patients undergoing ACLR alone or with a concomitant LET procedure (ACLR + LET) with a minimum graft diameter of 8mm that had either a 4S or 5S hamstring autograft configuration. The primary outcome was clinical failure, a composite of rotatory laxity and/or graft failure. The secondary outcome measures consisted of 2 patient-reported outcome scores (PROs)—namely, the ACL Quality of Life Questionnaire (ACL-QoL) and the International Knee Documentation Committee (IKDC) score at 24 months postoperatively. Results: Of the 618 patients randomized in the STABILITY study, 399 (228 male; 57%) fit the inclusion criteria for this study. Of these, 191 and 208 patients underwent 4S and 5S configurations of hamstring ACLR, respectively, with a minimum graft diameter of 8mm. Both groups had similar characteristics other than differences in anthropometric factors—namely, sex, height, and weight, and Beighton scores. The primary outcomes revealed no difference between the 2 groups in rotatory stability (odds ratio [OR], 1.19; 95% CI, 0.77-1.84; P = .42) or graft failure (OR, 1.13; 95% CI, 0.51-2.50; P = .76). There was no significant difference between the groups in Lachman ( P = .46) and pivot-shift ( P = .53) test results at 24 months postoperatively. The secondary outcomes revealed no differences in the ACL-QoL ( P = .67) and IKDC ( P = .83) scores between the 2 subgroups. Conclusion: At the 24-month follow-up, there were no significant differences in clinical failure rates and PROs in an analysis of patients with 4S and 5S hamstring autografts of ≥8mm diameter for ACLR or ACLR + LET. The 5S hamstring graft configuration is a viable option to produce larger-diameter ACL grafts.